Physical and Biological Responses to an Alternative Removal Strategy of a Moderate‐sized Dam in Washington, USA. (11th August 2015) - Claeson, S. M.; Coffin, B.
Abstract: Dam removal is an increasingly practised river restoration technique, and ecological responses vary with watershed, dam and reservoir properties, and removal strategies. Moderate‐sized dams, like Hemlock Dam (7.9 m tall and 56 m wide), are large enough that removal effects could be significant, but small enough that mitigation may be possible through a modified dam removal strategy. The removal of Hemlock Dam in Washington State, USA, was designed to limit channel erosion and improve fish passage and habitat by excavating stored fine sediment and reconstructing a channel in the former 6‐ha reservoir. Prior to dam removal, summer daily water temperatures downstream from the dam increased and remained warm long into the night. Afterwards, a more natural diel temperature regime was restored, although daily maximum temperatures remained high. A short‐lived turbidity pulse occurred soon after re‐watering of the channel, but was otherwise similar to background levels. Substrate shifted from sand to gravel–cobble in the former reservoir and from boulder to gravel–cobble downstream of the dam. Initially, macroinvertebrate assemblage richness and abundance was low in the project area, but within 2 years, post‐removal reaches upstream and downstream of the dam had diverse and abundant communities. The excavation of stored sediment and channel restoration as part of the dam removal strategy restored river continuity and improved benthic habitat while minimizing downstream sedimentation. This study provides a comparison of ecological effects with other dam removal strategies and can inform expectations of response time and magnitude. Published 2015. This article is a U.S. Government work and is in the public domain in the USA.